A 3 month nutrition and exercise program improved hallux strength among senior daycare center users in Korea: a cluster randomized controlled trial - Sim, Jiwon; Lim, Jongguk; Lee, Hayoung; Park, Sohyun; Shin, Dongsoo (Frontiers in Public Health, 2024)
Introduction With a growing aging population, the focus on the health and well-being of older adults, especially in preventing falls, becomes crucial. This 3 month study, initiated in July 2022, aimed to assess the impact of a nutrition and exercise program in senior daycare centers in Chuncheon, South Korea. Methods A 3 month study, beginning in July 2022, included 204 older adults from 10 senior daycare centers in Chuncheon, South Korea. Randomly assigned to intervention or control groups, the intervention involved nutrition, daily toe exercises, or both. Control centers received interventions post-measurements. Pre- and post-intervention analyses used paired t-tests and multiple linear regression, assessing metrics like toe grip strength for significance. While 204 were initially enrolled, the analysis included 151 participants due to dropouts. Results Participants, with a mean age of 83.3 years (43.1% aged ≥ 85 years), exhibited mild to moderate cognitive impairment and multiple chronic illnesses. Health data indicated that 37.3% were obese, and the average BMI was 24.0 kg/m2. Both the intervention and control groups showed significant improvements in toe grip strength post-intervention. Specifically, the exercise-only and combined exercise-nutrition groups demonstrated significant differences in hallux strength compared to the control group after adjusting for age and gender. Conclusion The study showed that a basic nutrition and exercise program increased toe strength in older adults with chronic diseases, including mild cognitive impairments. This intervention holds potential to prevent muscle strength decline and reduce fall risks in older individuals. As the first of its kind in Korean senior daycare centers, it emphasizes the need for future research and standardized programs for senior daycare users.